Design analysis of monitoring and inventory management at Public Elementary School Kalikajar Wetan Paiton - Bambang, Bambang; Shudiq, Wali Ja'far; Sholehah, Aisyatus; Fawaid, Izzah Diyanah; Maghfirah, Lidya Erika (Institute of Computer Science (IOCS), 2024)
This study aims to analyze and design an effective monitoring and inventory management system at Public Elementary School Kalikajar Wetan, Paiton. A well-structured inventory management system is crucial to ensure efficient asset management, reduce the risk of loss, and improve operational effectiveness. The research methods employed include direct observation, in-depth interviews with school staff, and a literature review on inventory management systems. The analysis of the existing system revealed several shortcomings in the manual recording method, such as data inaccuracies, potential duplication of information, and delays in inventory reporting. As a solution, this study proposes the design of a digital system featuring automated recording, real-time data updates, and organized data access. This system design is expected to enhance efficiency, accuracy, and transparency in the school's inventory management. The findings indicate that implementing the proposed system supports faster decision-making, minimizes errors, and provides convenience in monitoring overall assets. Thus, the design holds significant potential as a model for inventory management in other educational institutions.